CLINICAL AND DIAGNOSTIC STUDIES of MYCOPLASMA WENYONII INFECTION IN DEER OF BASRAH, IRAQ (Indian Journal of Animal Production and Management, 2025)
Clinical, hematological, biochemical, and molecular studies have been conducted and implemented for Hemomycoplasmosis (Haemoplasma) caused by Mycoplasma wenyonii, which was diagnosed in diseased anemic deer. Thirty-five (53) deer in Basrah, Iraq, exhibited signs of anemia, pyrexia, and panting. The causative organism was identified through Giemsa-stained blood smears and confirmed by PCR, with all tested samples yielding positive results (100%). Diseased deer showed various clinical signs, including loss of appetite (98.11%), enlargement of superficial lymph nodes (86.79%), anemia with pale mucous membranes (81.14%), panting with decreased performance (75.47%), and rough skin (64.15%). A significant reduction in blood indices, including total erythrocyte count, hemoglobin concentration, and packed cell volume, indicated normocytic normochromic anemia. Additionally, leukocytosis due to lymphocytosis and monocytosis was observed. Erythrocyte sedimentation rate (ESR) values were also elevated in diseased deer. Significant differences were found in clotting factor values. Furthermore, marked hypoproteinemia was detected in affected deer, along with a notable increase in total and indirect bilirubin, gamma glutamyl transferase (GGT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP). It is concluded that Hemomycoplasmosis continues to circulate among most domestic animals, including deer. Therefore, the development of effective control programs should commence.
Keywords: Mycoplasma wenyonii; deer; PCR; Basrah; Iraq